1973
DOI: 10.1136/jnnp.36.4.661
|View full text |Cite
|
Sign up to set email alerts
|

Significance of plasma lysolecithin in patients with multiple sclerosis: a longitudinal study

Abstract: SUMMARY Five patients with multiple sclerosis and four normal subjects have been followed for over two years. Plasma phospholipid levels and phospholipid fatty acid composition have been assayed periodically. The increased amount of plasma lysolecithin already described by us has been confirmed in this longitudinal study. A significant increase in saturated fatty acids of lysolecithin has also been demonstrated. In contrast, the lecithin concentration and fatty acid composition do not show any significant vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…We then elucidated the nature of the soluble signal by factor removal experiments using mass spectrometry lipidomics to identify that the lipid was lysophosphatidylcholine (LPC). Our findings have been supported by previous studies where, increased LPC levels have been observed in multiple sclerosis and in aged human brain (Andreoli et al, 1973;Wender et al, 1988). However, the precise mechanism behind LPC production has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…We then elucidated the nature of the soluble signal by factor removal experiments using mass spectrometry lipidomics to identify that the lipid was lysophosphatidylcholine (LPC). Our findings have been supported by previous studies where, increased LPC levels have been observed in multiple sclerosis and in aged human brain (Andreoli et al, 1973;Wender et al, 1988). However, the precise mechanism behind LPC production has not been fully elucidated.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that the demyelinating effect of LPC is due to the LPC molecule as such and not to metabolites [20]. In the case of MS, an increase in plasma levels of LPC has been reported [7], and the saturated fatty acid content of plasma LPC in MS patients is greater than that of LPC in controls [8], Whether altering the fatty acid content of patients' LPC could modify the severity of episodic demyelination re mains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…One possible candidate for such a bystander role is lysolecithin (lysophosphatidyl choline or LPC). An increase in the plasma level of LPC has been reported in MS patients [7], Furthermore, an increase in the saturated fatty acid content of LPC of MS patients compared with normal individuals has been reported [8], It is not known whether the different fatty acid content of LPC has any effect on the severity of an episode of demyelination in MS patients. We have therefore studied the myelinotoxic properties of LPC of different fatty acid composition in an animal model (the peripheral nerve of the rat), to see if lipid constitution might influence the degree of demyelin ation.…”
Section: Introductionmentioning
confidence: 99%
“…For definitive identification, the attractant in fraction 6 was compared with enzymatically prepared 1-palmitoyl-sn-glycerol-3-phosphorylcholine (L-palmitoyl-LPtdCho), the most abundant form of LPtdCho in human plasma (15). When fraction 6 was compared with L-palmitoyl-LPtdCho at equivalent concentrations oforganic phosphorus, the attractant activities ofthe preparations for 6C3HED cells were nearly identical (Fig.…”
mentioning
confidence: 97%